Peningkatan Pemahaman Communication Skills dan Personal Branding Bagi Siswa MA Al ‘Imaroh - Satim Hamid; Ririn Uke Saraswati; Jon Edy; Dede Rahmat; Alfian Mubarok; Ati Luliani; Linda Parwati; Fikry Dwi Seftian; Muhammad Cahya Nira (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
The community service seminar activity with the title “Increasing Understanding of Communication Skills and Personal Branding for MA Al Imaroh Students” was carried out with the aim of improving students' communication skills and self-image. This seminar was attended by 44 participants from the total number of students, and the evaluation results showed that there was an increase in understanding by 100%.Through interactive methods and hands-on practice, students are given the knowledge and skills needed to develop effective communication skills and build positive personal branding. In this activity, students were given training on how to create an attractive CV. This activity not only provides new insights, but also encourages students to apply the skills acquired in everyday life, both in the school environment and in the community.Thus, this seminar successfully achieved its objectives and is expected to be a model for other community service activities in the future.